Tomasz Kozłowski, Koniec imperium MSW. Transformacja organów bezpieczeństwa państwa 1989–1990, Warsaw: Instytut Pamięci Narodowej, 2019. An Overview - Bereszyński, Zbigniew (Institute of National Remembrance Review, 2025)
The book under review here, Koniec imperium MSW. Transformacja organów bezpieczeństwa państwa 1989–1990 by Tomasz Kozłowski, is the first book-length publication devoted entirely to the transformation within the Polish apparatus of internal affairs during 1989–1990. It covers the background, course and results of that process. The author offers a critical verification of popular ideas about the transition from the Security Service (SB) and the Citizens’ Militia (MO) to the Office of State Protection (UOP) and the Police. The publication features little-known or previously unavailable historical sources. The book has a major significance for understanding not just the premises and mechanisms of reorganisation in the interior apparatus, but also the mechanisms of transformation in Poland as a whole.